Los cuatrocientos golpes - Truffaut, François 1932-1984; Maurier, Claire; Rémy, Albert; Léaud, Jean Pierre (Regia Films, 2011)
Intensely touching story of a misunderstood young adolescent who left without attention, delves into a life of petty crime